2021
DOI: 10.1155/2021/7030656
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Rural Cultural Service System Based on Mobile Information System

Abstract: At present, the development of rural culture is gradually rising. Under the promotion of the sense of freedom and democracy, mobile information system also plays an important role in rural cultural services. This paper uses edge algorithm to build mobile information system, combined with rural cultural service elements, to carry out information construction for the people’s needs of tourism, information, and belief culture in the development of rural China. In this paper, with the county or township service pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Danbatta, S. J. et al simulated the number of tourists in Öki for the period 2004-2020 using a hybrid artificial neural network combined with a term Fourier transform, showing that the model was able to provide data-accurate analysis for the degree to which the city's tourism culture is favored by tourists [14]. Qu, X. et al based on a mobile information system algorithm and combined with rural cultural tourism services for rural tourism informatization construction, through mobile information interconnection can help villages better enhance their destination image and promote the development of rural tourism culture [15]. Xin, H. used remote sensing technology to analyze the integrated response characteristics of the thermal environment and spatial analysis of adaptation in the process of urbanization, indicating that urban tourism culture suffered a certain degree of destruction in the process of urbanization [16].…”
Section: ) City Tourism Culturementioning
confidence: 99%
“…Danbatta, S. J. et al simulated the number of tourists in Öki for the period 2004-2020 using a hybrid artificial neural network combined with a term Fourier transform, showing that the model was able to provide data-accurate analysis for the degree to which the city's tourism culture is favored by tourists [14]. Qu, X. et al based on a mobile information system algorithm and combined with rural cultural tourism services for rural tourism informatization construction, through mobile information interconnection can help villages better enhance their destination image and promote the development of rural tourism culture [15]. Xin, H. used remote sensing technology to analyze the integrated response characteristics of the thermal environment and spatial analysis of adaptation in the process of urbanization, indicating that urban tourism culture suffered a certain degree of destruction in the process of urbanization [16].…”
Section: ) City Tourism Culturementioning
confidence: 99%
“…In addition, Duan, H. In order to promote the development of the rural tourism industry, based on the reform of the rural tourism industry chain in the new normal of Internet+ and cross-border integration, and through empirical research on the factors affecting the consumers' agro-tourism products, which shows that Internet+rural tourism is a new mode, which will promote the transformation and upgrading of the leisure agriculture industry [17], in order to solve the problems of inefficiency, irrational development and overall tourism environment, based on the innovative idea of "big data + rural tourism" development, we put forward the theory of coordination and coupling of the current situation of rural tourism economy and industry and empirically demonstrated that efficiency and competitiveness are positively related to each other in rural tourism [18]. Qu, X. et al in order to meet the informatization needs in rural cultural construction, explored the project support degree of rural cultural service mobile information system and the satisfaction degree of residents' needs for various cultural resources through a questionnaire survey and found that the rural cultural service system built in rural cultural construction and tourism can basically meet the needs of life [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rong Ai, Jianwei Song and Xiaowei Xie. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] …”
mentioning
confidence: 99%
“…Literature [9] analyzes the fuzzy computing theory of the operating characteristics of complex systems in pastoral areas. Literature [10] combines the elements of rural cultural services, using edge algorithms to build a mobile information system to build information on the needs of tourism, information, and faith culture for rural development in China.…”
Section: ) Digital Rural Constructionmentioning
confidence: 99%